Negotiating Inclusive Campus Culture for Peaceful Coexistence: Religion, Power, and Identity in Islamic Higher Education - Agussalim; Akhsan; Nur Kaylah; Ihwan Ridwan; Kalsum (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2026)
This study examines how inclusive campus culture is negotiated in Islamic higher education in Indonesia and Malaysia as a mechanism for fostering peaceful coexistence and preventing violence, radicalism, and identity-based discrimination. While both countries have advanced institutional agendas of religious moderation in Indonesia and wasatiyyah in Malaysia, existing scholarship has largely treated these agendas as normative, curricular, or policy-based interventions, with limited attention to how inclusion is enacted as a lived institutional process shaped by religion, power, and identity. Using a mixed-methods design, this study combines survey data, semi-structured interviews, and focus group discussions conducted in selected Islamic higher education institutions in Indonesia and is complemented by comparative insights from Malaysian higher education contexts. The quantitative component analyzes the influence of knowledge of inclusive values and social tolerance behavior on the implementation of inclusive campus culture, while the qualitative component explores how institutional authority, identity relations, and everyday practices shape inclusion, recognition, and protection on campus. The findings show that knowledge of inclusive values and social tolerance behavior significantly influence the implementation of inclusive campus culture, with the cognitive dimension emerging as the stronger determinant. More importantly, the study demonstrates that inclusive campus culture functions as a negotiated institutional process in which religious values are translated into governance practices, power relations shape access to safety and recognition, and identity positions influence vulnerability and belonging. In this sense, violence, radicalism, and identity-based discrimination are not isolated phenomena, but manifestations of uneven inclusion within campus life. Theoretically, the study advances an integrative analytical framework linking religion, power, and identity to the institutional production of inclusive campus culture in Islamic higher education. Globally, it contributes to debates on peaceful coexistence by showing that preventing radicalism in Muslim-majority higher education contexts requires not only doctrinal moderation or security approaches, but also the institutionalization of inclusive cultures that enable recognition, participation, and protection across diverse identities.